Characteristics of water distribution and preferential flow processes and nutrient response on dolomite slopes in the southwestern karst region - Duan, Xiaoqian; Fu, Zhiyong; Deng, Yusong; Chen, Hongsong (Frontiers in Environmental Science, 2025)
Understanding the characteristics of the soil water content and preferential flow is critical for a thorough comprehension of soil nutrient loss in Karst slopes/ecosystems. We monitored the soil water content and soil temperature at 0–20, 20–40, and 40–60 cm depths on a typical Karst dolomite slope at a high frequency to determine the water distribution characteristics and confirm the occurrence of preferential flow from 2018 to 2021. The soil properties and nutrients in different soil layers during the rainy and dry seasons were determined along the slope (from upper to lower slope positions, with a total of 9 sampling sites). The results revealed that the saturated hydraulic conductivity of the soil at the upper slope position was significantly (p < 0.05) greater than that at the middle and lower slope positions. The soil water content at the down slope position was greater than that at the middle and upper slope positions, further more, coupling monitoring of the soil water content and temperature revealed obvious preferential flow in the Karst dolomite slope. In addition to the spatial variability in the water content, the soil nutrients exhibited regular spatial variations. The dissolved organic carbon (DOC), dissolved organic nitrogen (DON), total nitrogen (TN), total phosphorus (TP) and total potassium (TK) contents were the lowest at the upper slope position and the highest at the down slope position, whereas the difference in nutrients between the rainy and dry seasons was the greatest at the upper slope position. Our results demonstrated that the patterns of the soil water content and surface nutrient loss are consistent along the Karst dolomite slope and are related to the occurrence of preferential flow. Furthermore, the results suggested that, compared with those in previous studies, which focused only on soil properties in the Karst regions of Southwest China, the variation in the soil water content and occurrence of preferential flow may be more important than previously assumed.